Stereolithography-based antennas for satellite communications in Ka-Band - Silva, J. S.; García-Vigueras, M.; Debogovic, T.; Costa, J. R.; Fernandes, C. A.; Mosig, J. R. (Proceedings of the IEEE, 2017)
This paper illustrates the role of additive manufacturing (AM) as enabling technology to realize high-performance low-cost antennas for Ka-band applications. In addition to the inherent electromagnetic challenges implicit in the conception of such complex devices, this paper also points out the stringent limitations that appear when opting for classical fabrication techniques, based on assembled split-block models. AM emerges in this context as a change of paradigm, allowing monolithic fabrication and design freedom, which result in substantial improvements in terms of compactness, mass, simplicity, cost, and production time. Two different antennas for Ka-band satellite communications are presented here, namely a wideband horn and a dual-band circular cavity. Both prototypes are fabricated using a stereolithographic (SLA) AM process followed by metal coating. This fabrication approach is especially well suited to the implementation of these designs, since they have internal shapes that are inaccessible to conventional machining tools. The experimental results are not only in very good agreement with the theoretical predictions but also demonstrate improvements over the performances achieved by traditional milling and assembly fabrication approaches, thereby confirming the validity and great potential of SLA for Ka-band satellite communications.